Evidence-Based Diagnosis and Management of Facial Nerve Disorders - Volk, Gerd Fabian; Eisenhardt, Steffen U.; Rozen, Shai M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With increasing speed, new diagnostic and therapeutic approaches for facial nerve disorders are being published. Many of them have improved decision-making, treatment, and the rehabilitation of patients. Unfortunately, there is often a lack of high-quality studies that prove long-term effects or identify subgroups that are of particular benefit. Even a reliable characterization of patients with facial nerve disabilities is often complicated. Therefore, evidence-based management remains challenging. With this Special Issue on the topic of "Evidence-Based Diagnosis and Management of Facial Nerve Disorders", we have brought together experts from various fields, including speech pathology, plastic surgery, otolaryngology, neurology, and physical therapy, to present the latest developments in relation to facial nerve disorders and to present a great variety of topics to our readership. We can see that the topic of facial nerve palsy offers a vast and dynamic spectrum of developments, and hope that the research presented in this Special Issue shows the importance of a multidisciplinary approach. We hope it will not only enhance our knowledge of this condition, but also ultimately improve patient outcomes and their quality of life to some extent.